Prosecutorial Application of Restorative Justice: Overview, Mechanism, and Commentary on Prosecution Cessation - Jefferson Hakim; Azeem Marhendra Amedi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
This article discusses the implementation of prosecution cessation based on restorative justice by the Indonesian Public Prosecution Service. Restorative justice was introduced as an out-of-court criminal case settlement with certain conditions. Nevertheless, an unpopular opinion against the implementation of the prosecution cessation based on restorative justice as it is considered to deviate from the Indonesian Criminal Procedure Code. The purpose of the research in this article is to describe the concept of restorative justice, the implementation of the prosecution cessation based on restorative justice by the Indonesian Public Prosecution Service, as well as a juridical study of the implementation of prosecution cessation based on restorative justice in the perspective of the Indonesian Criminal Procedure Code. The research method in this article is normative juridical. Restorative justice is considered to be able to meet a sense of justice for the victim and society, as the perpetrator is required to be responsible for restoring the victim's condition to its original state by prioritizing mediation and dialogue. Coming from the perspective of the Indonesian Criminal Procedure Code, the implementation of stopping the prosecution based on restorative justice has the potential to become an object of pretrial. However, from the perspective of the idea of law, the prosecution cessation based on restorative justice satisfies the triad of justice and utility as the idea of law.